2016
DOI: 10.2134/jeq2015.09.0499
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Runoff from Land Application of Composted Poultry Litter

Abstract: Regions with long-term animal manure applications based on nitrogen (N) requirements have concerns regarding elevated nutrient levels. Most attention has focused on phosphorus (P), but heavy metal accumulation has received attention due to perceived environmental concerns. Composting is a potential management practice that can reduce total manure mass and volume while creating a stabilized product that has less odor and fewer pathogens. However, composting animal manures can lead to high N loss via ammonia vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…In 2013, 42 drinking water associated outbreaks occurred in the US resulting in 1,006 cases of illness and 13 deaths primarily due to Legionella, Cryptosporidium, and Giardia (Braeye et al, 2015). Poultry farms in particular have been shown to cause increases in copper, zinc, potassium, and other nutrients concentrations into nearby rivers due to runoff of poultry litter (DeLaune and Moore, 2016;Sharpley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, 42 drinking water associated outbreaks occurred in the US resulting in 1,006 cases of illness and 13 deaths primarily due to Legionella, Cryptosporidium, and Giardia (Braeye et al, 2015). Poultry farms in particular have been shown to cause increases in copper, zinc, potassium, and other nutrients concentrations into nearby rivers due to runoff of poultry litter (DeLaune and Moore, 2016;Sharpley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Large storms often occurred shortly after poultry litter application in those studies, thus representing the worse‐case scenario for nutrients and metals in runoff. DeLaune and Moore (2016) also reported high Cu concentrations in runoff water from pastures that received poultry litter as fertilizer source.…”
Section: Resultsmentioning
confidence: 96%
“…This is because watershed models lack the routines to simulate fate and transport processes of metals. DeLaune and Moore (2016) conducted a runoff study on fescue pasture and compared the concentration of Zn and Cu in surface runoff among different treatments (e.g., plots fertilized with alum‐treated litter, fresh litter). In our study, the concentrations of Zn and Cu in surface runoff from plots with surface‐applied broiler litter were within the range of Zn and Cu concentrations in surface runoff reported by DeLaune and Moore (2016).…”
Section: Resultsmentioning
confidence: 99%
“…Moore et al (1998) reported that treatment of broiler litter with aluminum sulfate can reduce concentrations of Zn, Fe, Cu, and As in surface runoff. DeLaune and Moore (2016) reported that composting poultry litter decreased soluble Cu concentration in surface runoff. Furthermore, broiler litter application rate and timing to tall fescue ( Festuca arundinacea Schreb.)…”
mentioning
confidence: 99%